Immunological axis of curcumin-loaded vesicular drug delivery systems. (5th April 2018) - Chellappan, Dinesh K; Ng, Zhao Yin; Wong, Jin-Ying; Hsu, Alan; Wark, Peter; Hansbro, Nicole; Taylor, Jack; Panneerselvam, Jithendra; Madheswaran, Thiagarajan; Gupta, Gaurav; Bebawy, Mary; Hansbro, Philip M; et al.
Several vesicular systems loaded with curcumin have found their way in the therapeutic applications of several diseases, primarily acting through their immunological pathways. Such systems use particles at a nanoscale range, bringing about their intended use through a range of complex mechanisms. Apart from delivering drug substances into target tissues, these vesicular systems also effectively overcome problems like insolubility and unequal drug distribution. Several mechanisms are explored lately by different workers, and interest over vesicular curcumin has been renewed in the past decade. This commentary discusses several immunological targets in which curcumin is employed in a vesicular form.